Martin, Craig. 2021. Discourse and Ideology: A Critique of the Study of Culture - LeVasseur, Todd (Fieldwork in religion, 2023)
Martin, Craig. 2021. Discourse and Ideology: A Critique of the Study of Culture. New York: Bloomsbury Academic. 296 pp. ISBN 9781350246287 (pbk). $31.45.